Combinatorial Thinking in Mathematics Classrooms: A Systematic Literature Review on Current Trends and Pedagogical Implications - Gusti Uripno; Puji Rahayu; Edy Nurfalah (Universitas Tidar, 2026)
Combinatorial thinking, the cognitive capacity to systematically enumerate, structure, and reason about discrete arrangements, constitutes a foundational yet persistently challenging domain in mathematics education. This systematic literature review (SLR), conducted in accordance with the PRISMA 2020 guidelines, synthesises 15 empirical and theoretical studies published between 2004 and 2021. Four research questions guided the review: (RQ1) What research trends characterise the field in terms of educational level, methodology, and topical focus? (RQ2) What cognitive strategies do students employ, and what difficulties do they encounter? (RQ3) What pedagogical implications and instructional recommendations does the literature yield? (RQ4) How do digital tools and technology-mediated contexts support combinatorial thinking development? Findings indicate that higher-education qualitative research dominates the field, organised around a coherent programme centred on Lockwood's model of combinatorial thinking. Key cognitive strategies identified include systematic listing, the set-oriented perspective, equivalence thinking, and guided reinvention of counting formulas. Persistent difficulties centre on inconsistent application of the multiplication principle and category confusion between ordered and unordered selection. Pedagogically, the review endorses guided reinvention sequences, multiple-solution tasks, and explicit verification-strategy instruction. Technology, particularly outcome listing environments and online reinvention tasks, emerges as a meaningful scaffold when aligned with deliberate instructional design.